PENYUSUNAN NOTASI MUSIK DENGAN MENGGUNAKAN ONSET DETECTION DAN FOURIER TRANSFORM PADA SINYAL AUDIO - , Anindita Suryarasmi; , Dr.-Ing. Mhd. Reza M. I. Pulungan, S.Si., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Musical notation is a written documentation of a music. Even though musical notation is widely used, not every musician know how to write a music notation. This work offers automatic musical notation generation using onset detection and fourier transform. Duration and pitch of the notes are two basic parameters that have to be known in order to generate music notation. Computer has the ability to recognize both. Using Short Time Fourier Transform on audio data, the frequency of the sound played can be captured. Onset detection method implemented to recognize the pattern by measuring the interval between two notes, and Fourier Transform to identify the pitch of the note. This work implemented both methods to recognize pitch and duration of the notes. Both data are used to create note object in order to create a music notation. The output of the system is a musicXML formatted file. This format allowed the output to be edited using software for music editor. Result shows high accuracy up to 98.01% for unpitched music instrument. Meanwhile, test on pitched music instrument only shows 59.86% accuracy.